Biological and physical approaches on the role of piplartine (piperlongumine) in cancer - Tiago Henrique (Nature Portfolio, 2020)
Abstract Chronic inflammation provides a favorable microenvironment for tumorigenesis, which opens opportunities for targeting cancer development and progression. Piplartine (PL) is a biologically active alkaloid from long peppers that exhibits anti-inflammatory and antitumor activity. In the present study, we investigated the physical and chemical interactions of PL with anti-inflammatory compounds and their effects on cell proliferation and migration and on the gene expression of inflammatory mediators. Molecular docking data and physicochemical analysis suggested that PL shows potential interactions with a peptide of annexin A1 (ANXA1), an endogenous anti-inflammatory mediator with therapeutic potential in cancer. Treatment of neoplastic cells with PL alone or with annexin A1 mimic peptide reduced cell proliferation and viability and modulated the expression of MCP-1 chemokine, IL-8 cytokine and genes involved in inflammatory processes. The results also suggested an inhibitory effect of PL on tubulin expression. In addition, PL apparently had no influence on cell migration and invasion at the concentration tested. Considering the role of inflammation in the context of promoting tumor initiation, the present study shows the potential of piplartine as a therapeutic immunomodulator for cancer prevention and progression.